Bringing Critical Race Praxis Into the Study of Electrophysiological Substrate of Sudden Cardiac Death: The ARIC Study. Issue 3 (4th February 2020) - Jensen, Kelly; Howell, Stacey J.; Phan, Francis; Khayyat‐Kholghi, Maedeh; Wang, Linda; Haq, Kazi T.; Johnson, John; Tereshchenko, Larisa G.
Abstract : Background: Race is an established risk factor for sudden cardiac death (SCD). We sought to determine whether the association of electrophysiological substrate with SCD varies between black and white individuals. Methods and Results: Participants from the ARIC (Atherosclerosis Risk in Communities) study with analyzable ECGs (n=14 408; age, 54±6 years; 74% white) were included. Electrophysiological substrate was characterized by ECG metrics. Two competing outcomes were adjudicated: SCD and non‐SCD. Interaction of ECG metrics with race was studied in Cox proportional hazards and Fine‐Gray competing risk models, adjusted for prevalent cardiovascular disease, risk factors, and incident nonfatal cardiovascular disease. At the baseline visit, adjusted for age, sex, and study center, blacks had larger spatial ventricular gradient magnitude (0.30 mV; 95% CI, 0.25–0.34 mV), sum absolute QRST integral (18.4 mV*ms; 95% CI, 13.7–23.0 mV*ms), and Cornell voltage (0.30 mV; 95% CI, 0.25–0.35 mV) than whites. Over a median follow‐up of 24.4 years, SCD incidence was higher in blacks (2.86 per 1000 person‐years; 95% CI, 2.50–3.28 per 1000 person‐years) than whites (1.37 per 1000 person‐years; 95% CI, 1.22–1.53 per 1000 person‐years). Blacks with hypertension had the highest rate of SCD: 4.26 (95% CI, 3.66–4.96) per 1000 person‐years. Race did not modify an association of ECG variables with SCD, except QRS‐T angle. Spatial QRS‐T angle was associated with SCD in whites (hazard ratio, 1.38; 95% CI, 1.25–1.53) and hypertension‐free blacks (hazard ratio, 1.52; 95% CI, 1.09–2.12), but not in blacks with hypertension (hazard ratio, 1.15; 95% CI, 0.99–1.32) ( P ‐interaction=0.004). Conclusions: Race did not modify associations of electrophysiological substrate with SCD and non‐SCD. Electrophysiological substrate does not explain racial disparities in SCD rate.